1993
DOI: 10.1002/zaac.19936191118
|View full text |Cite
|
Sign up to set email alerts
|

Schwefeldioxid als Ligand und Synthon. XII. Synthese und Reaktivität von Nickel(II)‐Komplexen dreizähniger anionischer Liganden des Typs (C6H3{CH2NR1R2}2‐2,6)

Abstract: Organonickel(II)‐Komplexe des Typs [NiX{C6H3(CH2NR1R2)2‐2,6}] (X = Halogen, OH2+/CF3SO3−; R1R2Et 1; R1R2iPr 2; R1 = Me, R2 = Cy 3; (NR1R2) = piperidino 4; (NR1R2) = pyrrolidino 5) werden beschrieben. Die Charakterisierung erfolgte mit Hilfe der 1H und 13C‐NMR‐ sowie der UV/Vis‐Spektroskopie. Von 1 a (X = Br) wurde die Kristallstruktur bestimmt. Dieser Komplex kristallisiert orthorhombisch in der Raumgruppe Pbca mit a = 1 335,8(2) pm, b = 1 903,3(3) pm, c = 1 365,4(3) pm und Z = 8, er besitzt eine annäher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…We prepared this ligand via a recently develw x oped enantioselective route 23 outlined in Scheme 2. The absolute stereochemistry of the product was hitherto unknown but has now been established by the structural characterization of 5 5 .…”
Section: Discussionmentioning
confidence: 99%
“…We prepared this ligand via a recently develw x oped enantioselective route 23 outlined in Scheme 2. The absolute stereochemistry of the product was hitherto unknown but has now been established by the structural characterization of 5 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Their Ni(II) complexes generally have a square-planar metal geometry with the direct M−C aryl σ-bond flanked by two, mutually trans-positioned, ortho-chelating, tertiary amino substituents. The group X is trans to the aryl unit . We have already reported that the para -substituent (R) influences the Ni(II)/Ni(III) redox potential in such aryldiaminenickel(II) complexes and we have shown that other modifications of the ligand system can influence (through both steric and electronic factors) both catalysis 11,15c and ligand coordination modes 15b…”
Section: Introductionmentioning
confidence: 99%
“…The controlled radical polymerization concept has been extended by Matyjaszewski and co-workers 7d,e for the bulk polymerization of styrene and MMA. This process uses a CuX/2,2‘-bipyridine catalyst which is similar to many of the Cu halide/amine systems that are used in Kharasch addition reactions. A recent report by Teyssié and collaborators details the similar use of the arylnickel(II) complex ( 1 ), first synthesized in this laboratory, ,15a in a similar manner for a well-controlled radical polymerization of MMA at rather moderate temperatures 7h. This report is highly relevant to the interpretation of the new results reported herein.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the Lewis basic character of NCN pincer complexes is strongly dependent on the functional groups on the donor sites. An increase in the steric bulk from E=NMe 2 to NEt 2 is sufficient to induce an efficient shielding of the metal z ‐axis and therefore prevents the formation of these Lewis acid–base complexes even though NEt 2 is more basic than NMe 2 (Scheme ) 30b, 56…”
Section: New Materials Propertiesmentioning
confidence: 99%